Implikasi Teori Percampuran Akad Mudharabah Dan Musyarakah Terhadap Perbankan Syariah (Studi Kasus Bank Syariah Mandiri KCP Sumenep) - Mujaddidi, Ahmad Shibghatullah (Jurnal Manajemen dan Inovasi (MANOVA), 2020)
This paper aims at describing the implications of the theory of mixing and its products towards Islamic banking and Islamic financial institutions. A qualitative research methods with a descriptive approach was implemented in this study. The object of the current study was Sub-Branch Office (KCP) of the Syariah Mandiri Bank in Sumenep Regency. The results of this study indicated that the products of the Syariah Mandiri Bank KCP Sumenep in terms of the Musharaka financing contract consists of Musharaka mutanaqishah and musharaka of network capital. Musharaka mutanaqisha is applied in home financing in which the profits are obtained from the margin agreed by all parties. While, the musharaka of network capital uses a profit sharing system in which the profits are calculated through a revenue sharing system. In terms of juridical law, the Syariah Mandiri bank KCP Sumenep has followed the rules stated in the Sharia banking law of 2008 as well as in the fatwa of the National Sharia Board. Whereas, in the case of the application of musharaka accounting that has been regulated in International Financial Report Standard (PSAK), Sharia Mandiri Bank KCP Sumenep has accordingly applied the contract accounting of musharaka as regulated in PSAK 106. However, in terms of account recording (estimation), Islamic banks have not obeyed the rules stated in PSAK 106. Furthermore, this study concludes that there are still many customers who do not understand the contract of mudharabah at Syariah Mandiri Bank KCP Sumenep. It due to the lack of socialization from the banks to the public. In juridical perspective, the Sharia Mandiri Bank KCP Sumenep do not implements mudharabah contract based on fatwa of the National Sharia Board and do not apply the accounting based on PSAK 105. Therefore, it is categorized as Islamic/ sharia financial engineering.